Električni in elektromehanski pretvorniki: Zapiski predavanj - Zagradišnik, Ivan; Ritonja, Jožef (2025)
First revised editionElectrical and Electromechanical Converters. The publication presents basics of electromechanical conversion and four fundamental electrical machines: transformer, induction machine, synchronous machine and commutator machine. The publication is organized in five chapters with contents as is written bellow. Introduction: magnetic field, windings, induced voltage, forces and torque, electrical and electromechanical conversions, losses, efficiency, heating, and cooling. Transformer: construction, basic principles of operation, ideal and real single-phase transformer, three-phase transformer, special types of transformers. Induction machine: description of construction, principle of steady state operations, starting of motors and changing of speed and torque, induction generator, single-phase induction motors. Synchronous machine: description of construction, principle of operation, working on an infinite bus, simplified description of the saturated machine, excitation systems and use of permanent magnets for excitation,synchronous motors with permanent magnets. Commutator machine: description of construction and operation, armature reaction, commutation problems, commutation with electronics, characteristics of different stator and rotor connection, changing of speed, alternating commutator machine.
Keywords: basics of electromagnetism; transformer; induction machine; synchronous machine; commutator machine